Kelangkaan Gas LPG 3 Kg Di Dukuh Kebumen, Kabupaten Pemalang - Ade Lia Novitasari; Farah Laili Laksita Windy; Friska Diah Mukaromah (Badan Penerbit STIEPARI Press, 2023)
It is no secret that 3 kg of LPG gas is difficult to obtain for the middle and popular classes. These products are often rare and their prices increase at the commercial level. In addition, LPG gas is also appreciated by the middle class. This study used qualitative methods and descriptive analysis. The results of the study show that up to three kilograms of LPG will be distributed to middle and low-income people who are registered with proof of KTP and KK. However, there are frauds from the foundation and poor staff, causing a shortage of 3 kg of LPG. LPG is also sold above the approved HET (highest retail price). This product is sold according to the supply and demand system, while the local government is not badin controlling the damage to the gas distribution system for the lower class of society. Therefore, market intelligence can always go beyondthe policies issued by the government.